2016
DOI: 10.1007/s10461-016-1287-z
|View full text |Cite
|
Sign up to set email alerts
|

The Acceptability and Perceived Usefulness of a Weekly Clinical SMS Program to Promote HIV Antiretroviral Medication Adherence in KwaZulu-Natal, South Africa

Abstract: Short message service (SMS) text messages have been used to remind and encourage patients to take ART in research studies. However, few studies have assessed the feasibility and acceptability of SMS in routine clinical practice. We report patient perspectives on a weekly SMS adherence support program after implementation into clinical care at an HIV clinic in KwaZulu-Natal, South Africa. We conducted structured interviews with a cross-sectional convenience sample of 100 adult patients who were invited to join … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 38 publications
4
42
0
Order By: Relevance
“…The majority of the quantitative surveys (54; 76.1%) were administered by an interviewer [100,102,104109,112,113,115117,119,121124,128130,133–137,139,141–150,152–166,168,169], five (7.0%) were self-administered [125,126,132,140,151], one (1.4%) used an audio computer-assisted self-interview [110] and the remaining studies (11; 15.5%) did not specify or it was not clear how the survey was administered [101,103,111,114,118,120,127,131,138,167,170]. No studies indicated clearly that there was a free response option for participants to report the barriers they experienced (for further description on the studies see the supplementary material).…”
Section: Resultsmentioning
confidence: 99%
“…The majority of the quantitative surveys (54; 76.1%) were administered by an interviewer [100,102,104109,112,113,115117,119,121124,128130,133–137,139,141–150,152–166,168,169], five (7.0%) were self-administered [125,126,132,140,151], one (1.4%) used an audio computer-assisted self-interview [110] and the remaining studies (11; 15.5%) did not specify or it was not clear how the survey was administered [101,103,111,114,118,120,127,131,138,167,170]. No studies indicated clearly that there was a free response option for participants to report the barriers they experienced (for further description on the studies see the supplementary material).…”
Section: Resultsmentioning
confidence: 99%
“…Some qualitative studies have reported that SMS recipients desired discreet, coded messages to prevent status disclosure (Curioso et al, 2009; Rana et al, 2015), while others reported a lack of consensus among recipients (Mbuagbaw, Bonono-Momnougui, & Thabane, 2012a), and desire by some for detailed information about HIV medication (Georgette et al, 2016). Most interventions to date have delivered SMS that do not overtly refer to HIV or medication, instead sending greetings (Lester et al, 2010), indirect reminders to ‘take care of health’ (da Costa et al, 2012; Pop-Eleches et al, 2011), or unrelated content such as news, weather or jokes (Hardy et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, simple SMS replies were an insufficient measure of receipt. Previous studies have shown higher levels of engagement when utilizing serial messaging and two-way communications [6,7,34,35], rather than one-time messaging. Including quizzes or trivia may also improve participant response rates [31].…”
Section: Discussionmentioning
confidence: 99%
“…Median age among adult participants was 27 years of age (interquartile range (IQR) [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] Step 2: SMS Received…”
Section: Study Population Of the Process Evaluationmentioning
confidence: 99%